(untitled) (International Journal of Nursing Education, 2020)
The Covid- 19 pandemic has forced the central and state governments to strictly adhere to complete lockdown in the country. In order to continue teaching and learning of Nursing students, Online learning was organized by Tamil Nadu Nurses and Midwives Council (TNNMC), in collaboration with nursing educational Institutions of Tamil Nadu. This study was undertaken to assess the Perceived Benefits and Barriers and of online learning, among Nursing faculty in Tamil Nadu. Method: A cross sectional, descriptive correlational study was conducted among 2375 faculty, who were selected through consecutive sampling technique, in nursing colleges of Tamil Nadu. Google survey forms were used to collect the data (Rating Scales on Perceived Benefits and Barriers of online learning). Results: Study findings revealed that, Mean scores of benefits of online learning is 80/100, (SD - 9.1)and barriers scores was 62/100 (SD-9.24). Conclusion: Overall study findings revealed that overall faculty had positive perception on benefits of online learning even though they were also concerned about some barriers which can be managed by meticulous planning and implementation of the system. Therefore it can be effectively incorporated in future also along with traditional teaching method to facilitate effective teaching and learning process.